2014
DOI: 10.1007/s13760-014-0304-0
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum vitamin D levels are associated with diabetic peripheral neuropathy in a rural area of Turkey

Abstract: Data examining the association between vitamin D and diabetic peripheral neuropathy are limited. This study investigated the serum levels of vitamin D, vitamin D-binding protein (VDBP), and vitamin D receptor (VDR) in diabetics in the Yozgat region of Turkey, and assessed their relationships with diabetic peripheral neuropathy. 69 diabetic patients and 49 age- and sex-matched control subjects were enrolled in this clinical prospective study. All the diabetics underwent conventional sensory and motor nerve cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 39 publications
6
27
0
2
Order By: Relevance
“…More importantly, this is the first study to demonstrate the screening value of low 25(OH)D level for DPN in Chinese patients with type 2 diabetes, as far as we know. In fact, this close relationship between vitamin D and DPN has been reported by other epidemiological studies of Caucasoid or Turkey population . Low blood 25OH‐D concentration was also associated with an increased risk of macrovascular and microvascular disease events in type 2 diabetes in a 5‐year observational study .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…More importantly, this is the first study to demonstrate the screening value of low 25(OH)D level for DPN in Chinese patients with type 2 diabetes, as far as we know. In fact, this close relationship between vitamin D and DPN has been reported by other epidemiological studies of Caucasoid or Turkey population . Low blood 25OH‐D concentration was also associated with an increased risk of macrovascular and microvascular disease events in type 2 diabetes in a 5‐year observational study .…”
Section: Discussionsupporting
confidence: 83%
“…It was revealed that the serum vitamin D levels were significantly lower, while the vitamin D receiver levels were higher, in diabetic patients than age‐ and sex‐matched control subjects. Besides, the serum vitamin D levels were reported significantly lower in patients with DPN than in those without . Latest study also indicated that vitamin D had an inverse association with both DPN presence and severity, as each 1 ng/mL increase in serum 25(OH)‐D was correlated with 2.2 and 3.4% decrease in the presence and severity of NCV impairment, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, about one-quarter of T1DM patients developed DPN with age, duration of diabetes, and poor glycemic control as leading risk factors [7]. Recently, accumulating studies have disclosed that some serum biomarkers, including uric acid and vitamin D, are associated with progression of DPN, the initial manifestation of T2DM [8,9]. Therefore, we hypothesized that identifying crucial cytokines in DPN development and their association with DPN is beneficial to the early diagnosis and personalized treatment for DPN patients.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Decreased serum vitamin D levels were also associated with diabetic peripheral neuropathy, which is an important reason for chronic pain. 30 A number of mechanisms have been proposed to explain the role of vitamin D deficiency in chronic pain syndromes. The most important mechanism related to pain is the Fig.…”
Section: Discussionmentioning
confidence: 99%